PENGAKUAN TRANSFER PERSEDIAAN ANTARA KANTOR PUSAT DAN CABANG PADA PANDEKA CHICKEN DAN PANDEKA COFFEE 2.0 - Putra, Yosep eka; Maharani, Khairunisa; Putri, Rani Meilani; Lestari, Winda Ayu; Andini, Nurmallah; Rahmi, Mega (Sekolah Tinggi Ilmu Ekonomi Yasa Anggana Garut, 2025)
This study aims to analyze the recognition of inventory transfers between the head office (Pandeka Chicken) and branch (Pandeka Coffee 2.0) and to examine its impact on the accuracy of financial reporting. The research employed a descriptive qualitative approach through observation, interviews, and documentation. The findings reveal that the inventory transfer process has not been supported by a standardized accounting system. There is no formal transfer documentation, no transfer pricing policy, and no calculation of cost of goods sold (COGS) at the branch level. In addition, several costs related to production were misclassified as operational expenses, depreciation was not recorded, and the internal control system over inventory remains weak. These conditions resulted in financial statements that do not reflect the actual condition of the business and hinder performance evaluation and financial consolidation between the head office and the branch. The study concludes that the lack of standardized recording procedures for inventory transfer increases the risk of financial misstatement and reduces the reliability of financial information for decision-making. The results provide recommendations for implementing transfer pricing, improving reporting integration, and strengthening internal control procedures.